2006
DOI: 10.1097/01.ico.0000208813.17367.0c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Cyclosporine 0.05% in the Treatment of Dry Eye Associated With Graft Versus Host Disease

Abstract: The findings in this prospective study suggest that dry eye associated with graft versus host disease can be effectively treated with topical cyclosporine, especially in patients unresponsive to other treatment modalities. These findings should be further evaluated in large-scale, controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 10 publications
0
30
2
Order By: Relevance
“…28,29 A previous noncontrolled trial in 8 patients with cGVHD dry eyes showed significant improvement of Schirmer basal secretion scores, TBUT and tear lysozyme levels after 3 months of treatment with 0.05% topical Cys. 30 Another retrospective noncontrolled study in 16 patients with cGVHD dry eye disease treated with 0.05% topical Cys showed significant improvements of symptom scores and vital staining after a mean follow up of 90 days. 31 The two studies showed increased Schirmer values, but the baseline Schirmer value in these two studies were much higher (from 7.274.0 mm to 11.372.2 mm after 3 months of treatment, from 8.0 mm to 8.5 mm after a mean follow up of 90 days) than the values reported in our study (from 3.473.1 mm to 4.774.5 mm after 1 month of treatment), suggesting a much more severe disease in our case compared to these two previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…28,29 A previous noncontrolled trial in 8 patients with cGVHD dry eyes showed significant improvement of Schirmer basal secretion scores, TBUT and tear lysozyme levels after 3 months of treatment with 0.05% topical Cys. 30 Another retrospective noncontrolled study in 16 patients with cGVHD dry eye disease treated with 0.05% topical Cys showed significant improvements of symptom scores and vital staining after a mean follow up of 90 days. 31 The two studies showed increased Schirmer values, but the baseline Schirmer value in these two studies were much higher (from 7.274.0 mm to 11.372.2 mm after 3 months of treatment, from 8.0 mm to 8.5 mm after a mean follow up of 90 days) than the values reported in our study (from 3.473.1 mm to 4.774.5 mm after 1 month of treatment), suggesting a much more severe disease in our case compared to these two previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…This study suggested that topical cyclosporine 0.05% treatment provided improvements in Schirmer test results, BUT scores, and tear lysozyme levels in patients with GVHD. 28 Wang et al 29 also investigated the effect of topical cyclosporine in patients with dry eye with chronic GVHD and suggested that improvements in the ocular surface and tear functions after 1 month of topical cyclosporine A emulsion therapy resulted from the decreased inflammation, increased goblet cell density, and MUC5AC messenger RNA expression.…”
Section: Discussionmentioning
confidence: 97%
“…8 Anti-inflammatory drugs such as topical steroids and cyclosporine eye drops have been shown to be effective in the therapy of cGVHD-related and non-cGVHD-related KCS. [8][9][10][11][12][13][14][15][16][17] The main therapeutic aim in the management of ocular cGVHD is therefore the treatment of both inflammation and dryness to relieve patients' symptoms and to maintain ocular integrity and function.…”
mentioning
confidence: 99%